The Volatile Oil of Zanthoxylum bungeanum Pericarp Improved the Hypothalamic-Pituitary-Adrenal Axis and Gut Microbiota to Attenuate Chronic Unpredictable Stress-Induced Anxiety Behavior in Rats - Wei D; Zhao Y; Zhang M; Zhu L; Wang L; Yuan X; Wu C (Dove Medical Press, 2021)
Daneng Wei,1,* Yafei Zhao,2,* Mengmeng Zhang,1 Lei Zhu,1 Li Wang,1 Xing Yuan,3 Chunjie Wu1 1Pharmacy College, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan 611137, People’s Republic of China; 2Acupuncture and Moxibustion College, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan 610075, People’s Republic of China; 3School of Medical and Life Sciences, Chengdu University of Traditional Chinese Medicine, Chengdu, Sichuan 611137, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xing YuanSchool of Medical and Life Sciences, Chengdu University of Traditional Chinese Medicine, No. 1166 Liutai Avenue, Wenjiang District, Chengdu, Sichuan 611137, People’s Republic of ChinaEmail yuanxing19891222@163.comChunjie WuPharmacy College, Chengdu University of Traditional Chinese Medicine, No. 1166 Liutai Avenue, Wenjiang District, Chengdu, Sichuan 611137, People’s Republic of ChinaEmail wucjcdtcm@163.comBackground: Anxiety disorders (ADs) are the most prevalent mental disorders worldwide. Stress-induced activation of the hypothalamic-pituitary-adrenal (HPA) axis and dysbiosis of gut microbiota seem to contribute to the onset of ADs. This study was designed to investigate the ameliorative effect of volatile oil of Zanthoxylum bungeanum (VOZB) on chronic unpredictable stress (CUS) induced anxiety behavior, as well as the altered HPA axis and gut microbiota.Methods: Experimental rats were exposed to the CUS for 14 consecutive days. Meanwhile, VOZB was administered at doses of 50, 100 and 200 mg/kg/day for 14 days. The anxiety behavior was evaluated by elevated plus-maze (EPM) and open field (OF). The protein expressions and mRNA levels of corticotropin-releasing hormone (CRH) and glucocorticoid receptor (GR) in hypothalamus was determined, as well the hormone levels of HPA axis in serum. Furthermore, gut microbiota was detected by16S rRNA gene sequencing. The chemical constituents of VOZB were identified by GC-MS analysis.Results: VOZB treatment (100 and 200 mg/kg/day) increased the ratio of open-arm entries and time in EPM test, as well as the central zone entries and time in OF test. Moreover, VOZB treatment reduced the protein expressions and mRNA levels of CRH, but elevated those of GR in hypothalamus. Similarly, the hormone levels of the HPA axis in serum were decreased by VOZB treatment. Besides, VOZB treatment restored the CUS-induced dysbiosis of gut microbiota, raising the Sobs and Chao indexes, inhibiting Lachnospiraceae, but facilitating Bacteroidales_S24-7_group, Lactobacillaceae, and Prevotellaceae. Additionally, Sobs and Chao indexes were negatively correlated to the serum corticosterone and CRH levels.Conclusion: VOZB showed an ameliorative effect on CUS-induced anxiety behavior, potentially via inhibiting activation of the HPA axis and restoring the dysbiosis of gut microbiota, thus improving the stress-induced abnormality of the microbiota-gut-brain axis.Keywords: Zanthoxylum bungeanum, anxiety disorders, stress, neuroendocrine, hypothalamic-pituitary-adrenal axis, gut microbiota